Non-timber Forest Product Use and Market Chains Along a Deforestation Gradient in Southwest Malawi - Mahonya, Sophie; Shackleton, Charlie M.; Schreckenberg, Kate (Frontiers in Forests and Global Change, 2019)
The importance of non-timber forest products (NTFPs) to rural livelihoods is widely acknowledged globally, as is the income generated from casual or fulltime trade in NTFPs on village and urban markets. However, there is less understanding of how the condition or status of the neighbouring landscapes and vegetation influence the use of and trade in NTFPs. Here we report on the use and trade in NTFPs in four villages situated along a gradient of decreasing forest cover in southwest Malawi using a mixed-methods approach. Data were sourced via a survey of 286 households, value chain analysis of the four most commonly traded NTFPs (thatch grass, edible orchids, mushrooms and wild fruits), key informant interviews with NTFP traders and direct observations. All households used at least one NTFP, with the most widely used ones being firewood (100% of households), bamboo (96%), thatch grass (94%), and timber for construction (92%). Overall, 15% of households sold at least one NTFP and the prevalence of selling within a village was correlated with forest cover, whereas buying of NTFPs was inversely correlated with forest cover. There was a wide range in mean annual income per product (US$20 – 456) from selling NTFPs based on the product, whether the trader sold on a casual or full-time basis and the market. Of those households selling NTFPs, approximately two-thirds sold more than one NTFP product, which is rarely recognised in income studies of individual single market chainsNTFP products. The returns to labour were variable between villages and products, but were generally double or more than the national minimum hourly wage. The NTFP value chains were short, dominated by traders and some intermediaries. Most of the products were sold in local markets with little value addition other than sorting and grading. Overall, NTFPs were an integral part of the household economy, with multiple participants and users, partly shaped by the forest cover of the surrounding landscapes.